2020
DOI: 10.3390/su12051962
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning European Protein-Rich Food Consumption and Production towards More Sustainable Patterns—Strategies and Policy Suggestions

Abstract: Global and European diets have shifted towards greater consumption of animal proteins. Recent studies urge reversals of these trends and call for a rapid transition towards adoption of more plant-based diets. This paper explored mechanisms to increase the production and consumption of plant-proteins in Europe by 2030, using participatory backcasting. We identified pathways to the future (strategies), as well as interim milestones, barriers, opportunities and actions, with key European stakeholders in the agri-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…The major weaknesses of plant-based food products identified in our study are high consumer prices, lack of similarity in taste and texture to traditional meat and dairy products, drawbacks in the development and application of new processing technologies, and limited product information in terms of labelling and marketing. These findings reinforce the idea that the widespread consumption of plant-based foods may be minimal if these products continue to be perceived as excessively expensive in comparison to traditional animal-based products [47]. In this sense, numerous studies have reported that high price is one of the main barriers to buying sustainable products [30,68], and also to substituting meat with novel plant-based alternatives [28,69].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The major weaknesses of plant-based food products identified in our study are high consumer prices, lack of similarity in taste and texture to traditional meat and dairy products, drawbacks in the development and application of new processing technologies, and limited product information in terms of labelling and marketing. These findings reinforce the idea that the widespread consumption of plant-based foods may be minimal if these products continue to be perceived as excessively expensive in comparison to traditional animal-based products [47]. In this sense, numerous studies have reported that high price is one of the main barriers to buying sustainable products [30,68], and also to substituting meat with novel plant-based alternatives [28,69].…”
Section: Discussionsupporting
confidence: 73%
“…In our study, interviews were limited to stakeholders from the stakeholder forum who are based within Spain (geographical scope of the study) and we used snowball sampling with stakeholders to identify other individuals to interview. More information about the P2F stakeholder forum and the MCM stakeholder consultation can be found in Manners et al [47] and Blanco et al [48]. Stakeholder groups were defined according to the breakdown used in the P2F stakeholder forum: (1) Producers (independent farmers, livestock owners, and relevant farmers' associations); (2) Processors (food industries, including the Small and Medium-sized Enterprises (SMEs) involved in P2F); (3) Distributors (food distributors' associations, supermarkets, grocery stores, restaurants); (4) Consumers (flexitarians or meat-reducers, which represent the biggest growth potential for plant-based protein products [49]); (5) Policy-makers (Official Departments of Agriculture, Health and Environment at national level and the EU Commission); (6) Researchers (from P2F project and other research institutions); (7) NGOs (environmental and food security-related).…”
Section: Frame the Problemmentioning
confidence: 99%
“…by policy, science, or business), or rather from a demand-pull (raised by social movements and worried citizens and consumers) or a combination of these forces. They may arise ‘pro-actively’ in view of horizon scanning and scenario building exercises of future food systems ( CSIROFutures, 2017 ; De Wilde, 2016 ; Hebinck et al, 2018 ; Manners et al, 2020 ; Rutter, 2012 ; van der Weele et al, 2019 ; WorldBank, 2019 ), or rather ‘reactively’ when sectors or countries are faced with intractable problems such as intensifying droughts. In terms of the mission set up, it is important to consider if the missions provide strong steering and close down innovation options or consider a wide range of solutions that allow to be tinkered with, as this will result in different operationalization strategies of the missions ( Janssen et al, 2020 ).…”
Section: Mission-oriented Agricultural Innovation Systems: What Whymentioning
confidence: 99%
“…Political action and dedicated support for the agricultural sector are required in order to incentivize changes in both production and consumption. This should include: (i) providing guidelines and establishing pilots for efficient and sustainable conversion of livestock production to plant production in collaboration with the farmer advisory services, (ii) targeting subsidies towards production of plant-based food commodities [47], coupled with (iii) implementing measures for increasing the capability, opportunity, and motivation of consumers that will make it easier and more acceptable for them to make a primarily plant-based and healthy diet the preferred choice [71][72][73], and iv) considering adopting a carbon tax on food, as suggested by the Danish Council on Climate Change [20]. New actors in the market, such as producers of plant-based alternatives to meat and dairy, can potentially accelerate this transition because they are not invested in maintaining the status quo as more established actors are [74].…”
Section: Discussionmentioning
confidence: 99%